Prognostic Role of Biomarkers for Pulmonary Arterial Hypertension Associated with Bronchopulmonary Dysplasia in Extremely Premature Infants - Chun Chen; Bingchun Lin; Meiqi Wang; Chuanzhong Yang (Applied Bionics and Biomechanics)
To explore the association of the biochemical markers after birth with BPD-PAH, factors independently predicting BPD-PAH risk were identified by multivariate logistic regression. Cut off values were determined by plotting receiver-operator curve (ROC), for the sake of dichotomizing continuous variables that showed independent relation with BPD-PAH risk. The results show that uric acid (UC) and blood urea nitrogen (BUN) contents markedly increased among infants experiencing BPD-PAH in comparison with those without BPD-PAH (11.6 vs. 9.7 mmol/L, P=0.006 and 482.0 vs. 249.0 μmol/L, P<0.001, separately). As shown by multivariate logistic regression, serum BUN levels (OR=1.143) and uric acid levels (OR=1.034) were important risk factors for BPD-PAH. Through a lot of experiments, the effectiveness and the advanced nature of the framework proposed in this paper are proved effectively. The framework proposed in this paper can provide some reference and thinking for follow-up research.